Physiology, Psychoacoustics and Cognition in Normal and Impaired Hearing - van Dijk, Pim; Başkent, Deniz; Gaudrain, Etienne; de Kleine, Emile; Wagner, Anita; Lanting, Cris (Advances in Experimental Medicine and Biology, 2016)
otorhinolaryngology; neurosciences; hearing